The Urgency of Implementing Non-Conviction Based Asset Forfeiture in Recovery of State Losses Due to Corruption - Itok Dwi Kurniawan; Soehartono Soehartono; Vincentius Patria Setyawan; Jose Gama Santos (PT. Multidisciplinary Press Indonesia, 2024)
Follow the asset is the right approach to use in eradicating corruption in this era. The trend of low verdicts for corruptors and the suboptimal recovery of assets resulting from corruption are reasons to prioritize confiscation of assets rather than criminalizing corruptors. The aim of this research is to analyze the importance of implementing Non-Conviction Based Asset Forfeiture in corruption regulations in Indonesia. The method used in writing this article is a normative legal research method with a conceptual approach. The results of this research are that the use of NCB can optimize the recovery of assets resulting from corruption because it does not depend on a complicated criminal case examination process. The defendant's fault is not a criterion for confiscating assets, but proving that the assets are illegal is the basis for confiscating assets.